Production and quality of zucchini seeds after applying sulphur as top dressing and organic compost at planting - Bardiviesso, Estefânia Martins [UNESP]; De Brito Lima Lanna, Natália [UNESP]; Aguilar, Ariel Santivañez [UNESP]; Bezerra, Sara Raissa Brito [UNESP]; Pelvine, Raíra Andrade [UNESP]; Freitas, Pâmela Gomes Nakada [UNESP]; da Silva, Francisca Zildélia [UNESP]; da Silva, Marcela Sant' Anna Cordeiro [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Southern Cross Publishing, 2020)
The recommendation of fertilization for zucchini (Cucurbita pepo) cultivation is usually made with no differentiation from the other cucurbit crops. Thus, there is a need to examine the doses of fertilizers used for zucchini production, as well as the suitability for cultivars, seasons, and cultivation regions. The aim of this study was to evaluate the influence of sulfur doses at topdressing fertilization and the supply of organic compost at planting on the production and quality of zucchini seeds. A total of eight treatments were studied in a randomized block design with a factorial scheme 4×2, corresponding to four sulfur doses at topdressing (0, 57, 114 and 173 kg ha-1 of S), in the presence (30 t ha-1) and absence of organic compost at planting. The fruits were harvested 62 DAT, and after harvest, the fruits remained in rest for 15 days in order to reach the uniformity of the physiological maturity of the seeds. The production characteristics evaluated were average fresh weight, diameter, dry weight and length of the fruits, fruit yield per plant, weight of a thousand seeds, number and seed weight. Regarding the seed quality, the percentage of germination, germination speed index, first count of the germination test, and electric conductivity, were evaluated. The supply of organic compost at planting had a positive effect on the production and physiological quality of the seeds of zucchini produced. The sulfur applied at topdressing improved the presence of the organic compost and also the production of seeds. Hence, it is recommended to apply 30 t ha-1 of organic compost at planting in association with 57 kg ha-1 of S at topdressing for higher seed yield and quality.
Keywords: Ammonium sulfate; Cucurbita pepo; Organic matter; Seed production; Vigor